A comprehensive survey of wnt and frizzled expression in the sea urchin Paracentrotuslividus. Issue 3 (18th March 2014) - Robert, Nicolas; Lhomond, Guy; Schubert, Michael; Croce, Jenifer C.; McClay, David; Ettensohn, Charles
Summary WNT signaling is, in all multicellular animals, an essential intercellular communication pathway that is critical for shaping the embryo. At the molecular level, WNT signals can be transmitted by several transduction cascades, all activated chiefly by the binding of WNT ligands to receptors of the FRIZZLED family. The first step in assessing the biological functions of WNT signaling during embryogenesis is thus the establishment of the spatiotemporal expression profiles of wnt and frizzled genes in the course of embryonic development. To this end, using quantitative polymerase chain reaction, Northern blot, and in situ hybridization assays, we report here the comprehensive expression patterns of all 11 wnt and 4 frizzled genes present in the genome of the sea urchin Paracentrotus lividus during its embryogenesis. Our findings indicate that the expression of these wnt ligands and frizzled receptors is highly dynamic in both time and space. We further establish that all wnt genes are chiefly transcribed in the vegetal hemisphere of the embryo, whereas expression of the frizzled genes is distributed more widely across the embryonic territories. Thus, in P. lividus, WNT ligands might act both as short‐ and long‐range signaling molecules that may operate in all cell lineages and tissues to control various developmental processes during embryogenesis. genesis 52:235–250. © 2014 Wiley Periodicals, Inc.